Nasopharyngeal teratoma, congenital diaphragmatic hernia and Dandy–Walker malformation – a yet uncharacterized syndrome. Issue 5 (10th August 2016) - Gupta, N.; Shastri, S.; Singh, P.K.; Jana, M.; Mridha, A.; Verma, G.; Kabra, M.
Abstract : An association of congenital diaphragmatic hernia, dandy walker malformation and nasopharyngeal teratoma is very rare. Here, we report a fourth case with this association where chromosomal microarray and whole exome sequencing (WES) was performed to understand the underlying genetic basis. Findings of few variants especially a novel variation in HIRA provided some insights. An association of congenital diaphragmatic hernia, dandy walker malformation and nasopharyngeal teratoma is very rare. Here, we report a fourth case with this association where chromosomal microarray and whole exome sequencing (WES) was performed to understand the underlying genetic basis. Findings of few variants especially a novel variation in HIRA provided some insights.